2021
DOI: 10.1016/j.ijscr.2021.105709
|View full text |Cite
|
Sign up to set email alerts
|

Vesicouterine fistula presenting with cyclical haematuria mimicking bladder endometriosis: A case report

Abstract: Highlights Vesicouterine fistula is pathological communication between the bladder and uterus or cervix. Symptoms of VUF were secondary amenorrhea and cyclic hematuria with history of previous cesarean section (concluded as Youssef’s syndrome). Surgical approach is contemplated as definitive management of the VUF following caesarean section. A group of women was able to have normal period after fistula repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Regarding postoperative care, a Foley transurethral catheter was left in place for 2–3 weeks after surgery in 92 (93.8%) patients. In six studies, 38,51,58,78,81,94 where a transvesical approach was adopted, a suprapubic cystostomy was performed. Only one study reported the use of intrauterine Foley catheter in one patient for 5 days after surgery, 65 and another study described the use of contraceptives for 1 year after surgery 85 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding postoperative care, a Foley transurethral catheter was left in place for 2–3 weeks after surgery in 92 (93.8%) patients. In six studies, 38,51,58,78,81,94 where a transvesical approach was adopted, a suprapubic cystostomy was performed. Only one study reported the use of intrauterine Foley catheter in one patient for 5 days after surgery, 65 and another study described the use of contraceptives for 1 year after surgery 85 …”
Section: Resultsmentioning
confidence: 99%
“…Because the fistula in the bladder was too small, cystoscopy performed at another hospital a year ago showed no fistula but only a small bulge at this site. Since the patient never experienced vaginal leakage, we hypothesized that the fistula might have a one-way valve function that allowed only menstrual blood to enter the bladder and not urine to enter the uterine cavity, which may be related to the one-way valve generated by the uterine isthmus sphincter [ 7 ]. In addition, a hyperechoic blood clot image was seen in the bladder cavity at the time of this patient's visit, suggesting that this may be the source of the blood in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…VUF is an uncommon abnormal communication between the uterus and bladder. Accounting for between 1–4% of all urogenital fistulas, it is usually a complication in patients with a history of lower segment caesarean section 2,3 . The symptoms of VUF may include cyclical hematuria or menouria, amenorrhea, and urinary incontinence, though diagnosis is frequently delayed due to difficulties in identifying the fistulous passage 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Accounting for between 1-4% of all urogenital fistulas, it is usually a complication in patients with a history of lower segment caesarean section. 2,3 The symptoms of VUF may include cyclical hematuria or menouria, amenorrhea, and urinary incontinence, though…”
mentioning
confidence: 99%